Copper-Catalyzed Aerobic Oxidative Carbocyclization Reactions of N-[(E)-Stilben-2-yl]amine Derivatives - Lu, Cheng-Yen; Chuang, Che-Ping (Synthesis, 2015)
A synthetic method for highly functionalized 2-quinolinones and quinolines has been developed. The copper(II)-catalyzed aerobic oxidative carbocyclization reactions of α-substituted N-[(E)-stilben-2-yl]acetamides, via the intramolecular carbocupration onto the alkenyl moiety, produced 3-substituted 2-quinolinones. Several useful functional groups including benzoyl, acetyl, cyano, and ethoxycarbonyl groups are compatible with the reaction conditions. This strategy was further applied to N-[(E)-stilben-2-yl]enamines to prepare 2,3-disubstituted quinolines in good yields.
Keywords: copper salts; oxidative; cyclization; N-[(E)-stilben-2-yl]amines; quinolines